Design of Patch antenna with Various shapes and various feeding techniques for IoT in the 2.45 GHz ISM Band - Harrou Meryama; Benkhadda Omaima; Saih Mohamed; Rhazi Youssef; Reha Abedelati (ITM Web of Conferences)
This paper introduces the design and feeding techniques of microstrip patch antennas with triangular, circular, and rectangular shapes, optimized for operation within the 2.45 GHz ISM band and tailored for IoT applications. The 2.45 GHz ISM band supports a variety of IoT protocols, including Bluetooth, Wi-Fi, Zigbee, Thread, and RFID, each offering distinct functionalities for applications ranging from smart home automation to advanced connected health systems. The study focuses on the pivotal role of feeding techniques in antenna performance, categorizing them into contact methods (such as coaxial feed and microstrip line) and non-contact methods (such as aperture coupling and proximity coupling). Utilizing the transmission line method for initial design and the method of moments for parameter optimization, the performance of each antenna shape is rigorously compared in terms of reflection coefficient, gain, and bandwidth. This comprehensive analysis provides valuable insights into the efficacy of different geometrical shapes and feeding mechanisms, empowering designers to select suitable configurations for specific IoT requirements, thus enhancing the development of efficient and reliable wireless communication solutions in the 2.45 GHz ISM band.